Pengaruh Islamic Advertising dan Muslim Hipsters Terhadap Keputusan Pembelian Produk Fesyen Muslim Pada Marketplace Shopee - Niluh Anik Sapitri (CV. Eureka Murakabi Abadi, 2023)
The researcher aims (1) to determine the effect of Islamic advertising on purchasing decisions for Muslim fashion products on the Shopee Marketplace in Pattallassang district. gowa (2) to find out the influence of Muslim hipsters on purchasing decisions for Muslim fashion products on the Shopee marketplace in Pattallassang, Kab. gowa (3) to determine the effect of Islamic advertising and Muslim hipsters on purchasing decisions for Muslim fashion products on the Shopee marketplace in Pattallassang, Kab. gowa. This research is a descriptive quantitative research, the data used is primary data with data collection techniques through population questionnaires used in this study all the people in Patalasang District, Kab. Gowa. The sampling technique used in this study was a purposive sampling method of 30 samples. The data analysis method uses multiple linear regression and the data analysis technique uses the IBM SPSS version 24 application. The results of this study indicate that (1) Islamic advertising has no significant effect on purchasing decisions, (2) Muslim hipsters have a significant effect on purchasing decisions, (3) simultaneously the two variables have a significant effect on purchasing decisions. The implications of this study show that Muslim hipsters are very influential on consumers before making a purchase decision.